क य (1-3i) / sqrt (1 + 3i) बर बर ह ?

क य (1-3i) / sqrt (1 + 3i) बर बर ह ?
Anonim

उत तर:

# (1-3i) / sqrt (1 + 3i) #

# = (- 2sqrt ((sqrt (10) +1) / 2) + 3 / 2sqrt ((sqrt (10) -1) / 2)) - (2sqrt ((sqrt (10) -1) / 2) + 3 / 2sqrt ((sqrt (10) +1) / 2)) म #

स पष ट करण:

स म न य र प स वर गम ल क # एक + द व # इस प रक र ह:

# + - ((sqrt ((sqrt (a + 2 + b ^ 2) + a) / 2)) + (b / abs (b) sqrt ((sqrt (a 2 + b ^ 2) -a) / 2)) i) #

द ख:

क म मल म # 1 + 3i #, द न व स तव क और क ल पन क भ ग सक र त मक ह, इसल ए यह Q1 म ह और इसम अच छ तरह स पर भ ष त प रम ख वर गम ल ह:

#sqrt (1 + 3i) #

# = Sqrt ((sqrt (1 ^ 2 + 3 ^ 2) +1) / 2) + sqrt ((sqrt (1 ^ 2 + 3 ^ 2) -1) / 2) म #

# = sqrt ((sqrt (10) +1) / 2) + sqrt ((sqrt (10) -1) / i) #

इसल ए:

# (1-3i) / sqrt (1 + 3i) #

# = ((1-3i) sqrt (1 + 3i)) / (1 + 3i) #

# = (1-3i) ^ 2 sqrt (1 + 3i)) / ((1 + 3i) (1-3i) # #

# = (1-3i) ^ 2 sqrt (1 + 3i)) / 4 #

# = 1/4 (1-3i) ^ 2 (sqrt ((sqrt (10) +1) / 2) + sqrt ((sqrt (10) -1) / 2) i) #

# = 1/4 (-8-6i) (sqrt ((sqrt (10) +1) / 2) + sqrt ((sqrt (10) -1) / 2) i) #

# = - 1/2 (4 + 3i) (sqrt ((sqrt (10) +1) / 2) + sqrt ((sqrt (10) -1) / 2) i) #

# = - 1/2 ((4sqrt ((sqrt (10) +1) / 2) -3sqrt ((sqrt (10) -1) / 2)) + (4sqrt ((sqrt (10) -1) / 2) + 3sqrt ((sqrt (10) +1) / 2)) i) #

# = (- 2sqrt ((sqrt (10) +1) / 2) + 3 / 2sqrt ((sqrt (10) -1) / 2)) - (2sqrt ((sqrt (10) -1) / 2) + 3 / 2sqrt ((sqrt (10) +1) / 2)) म #